2003
DOI: 10.1111/1467-9280.01433
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fear and Anger on Perceived Risks of Terrorism

Abstract: The aftermath of September 11th highlights the need to understand how emotion affects citizens' responses to risk. It also provides an opportunity to test current theories of such effects. On the basis of appraisal-tendency theory, we predicted opposite effects for anger and fear on risk judgments and policy preferences. In a nationally representative sample of Americans (N = 973, ages 13-88) fear increased risk estimates and plans for precautionary measures; anger did the opposite. These patterns emerged with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
300
10
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,114 publications
(348 citation statements)
references
References 25 publications
13
300
10
5
Order By: Relevance
“…Litteraturen tilsier også at holdninger til terror, og ikke minst frykten for å bli utsatt for terror, er relatert til alder (Lerner et al 2003). Argumentet er at unge mennesker kjenner seg mindre sårbare enn eldre mennesker, noe som i sin tur kan bidra til at yngre respondenter er mindre villige til å gi etter for en anmodning fra PST, sammenlignet med eldre respondenter.…”
Section: Empirisk Analyse Ii: Betyr Det Noe Hvem Innbyggerne Er?unclassified
“…Litteraturen tilsier også at holdninger til terror, og ikke minst frykten for å bli utsatt for terror, er relatert til alder (Lerner et al 2003). Argumentet er at unge mennesker kjenner seg mindre sårbare enn eldre mennesker, noe som i sin tur kan bidra til at yngre respondenter er mindre villige til å gi etter for en anmodning fra PST, sammenlignet med eldre respondenter.…”
Section: Empirisk Analyse Ii: Betyr Det Noe Hvem Innbyggerne Er?unclassified
“…The psychological distress and differences in the psychological distress-smoking relation as a function of race were examined using logistic regression for smoking status and linear regression for number of cigarettes smoked; in both, the key predictors were race, psychological distress, and the interaction of the two. In addition, given evidence that specific types of negative affect can have differing effects on cognition and behavior (Ellsworth & Scherer, 2003;Lerner, Gonzalez, Small, & Fischhoff, 2003;Lerner, Small, & Loewenstein, 2004), we conducted exploratory analyses using each individual K6 item rather than the overall measure in the analyses described above. Because smoking is associated with both low-arousal (e.g., depression) and high-arousal (e.g., anxiety) types of psychological distress (Covey et al, 1998;Lasser et al, 2000;Zvolensky & Bernstein, 2005), we also separately examined high-and low-arousal items.…”
Section: Analysis Strategymentioning
confidence: 99%
“…Briefly, ATF states that it is possible to experience conditions under which emotions of the same valence will have divergent effects. For example, it has been shown that anger triggered in one situation can evoke more optimistic risk estimates and risk-seeking choices in unrelated situations, whereas fear does the opposite: both fear and anger are described as states of feeling bad (Lerner, Gonzalez, Small & Fischhoff, 2003;Lerner & Keltner, 2001 (Smith & Ellsworth, 1985), and -depending on how each positive (or negative) emotion is coded -the likelihood of some specific course of action may vary (Lazarus, 1991;Scherer, 1999). Second, emotion carries with it certain motivational properties that spill over to subsequent judgments.…”
Section: The Appraisal-tendency Framework Of Emotionsmentioning
confidence: 99%